Opial-type Inequalities for Generalized Integral Operators With Special Kernels in Fractional Calculus - Samraiz, Muhammad; Afzal, Muhammad Arslan; Iqbal, Sajid; Kashuri, Artion (Communications in Mathematics and Applications, 2018)
In this article, we originate some new Opial-type inequalities on fractional calculus involving generalized Riemann-Liouville fractional integral, the Riemann-Liouville \(k\)-fractional integral, the \((k,r)\) fractional integral of the Riemann-type and the generalized fractional integral operator involving Hypergeometric function in its kernel. As special case of our general results we obtain the results of Farid et al. [7].